Low-Stress Bicycle Network Mapping: The District of Columbia's Innovative Approach to Applying Level of Traffic Stress. Issue 1 (2017) - Semler, Conor; Sanders, Meredyth; Buck, Darren; Graham, James; Pochowski, Alek; Dock, Stephanie
Washington, D.C., has been a national leader in the adoption of innovative bicycle facilities. However, with much of the low-hanging fruit already plucked (i.e., bicycle facilities already in place), the District Department of Transportation (DOT) needed a mechanism to prioritize investments. Thus the District DOT developed a bicycle level of traffic stress (LTS) map as part of a Multimodal Congestion Management Study. Existing roadway information, combined with an innovative geographic information system approach, was used to create the map and to prioritize and expedite the collection of supplemental roadway information. The results confirmed existing perceptions about the availability of bicycle facilities in the District and identified previously unidentified gaps in the overall bicycle network. In addition, the methodology used to develop the LTS network map provided a proof-of-concept for other jurisdictions to use as they look to develop their own LTS network maps. With this information, the District DOT can now prioritize future bicycle infrastructure investments. It also has a mechanism to update the LTS map as additional data are collected and new facilities are constructed.